Chemoselective acylation of benzimidazoles with phenylacetic acids under different Cu catalysts to give fused five-membered N-heterocycles or tertiary amides. Issue 37 (19th July 2016) - Mai, Shaoyu; Zhao, Yingwei; Song, Qiuling
Abstract : Chemoselective C–N bond formations via aerobic oxidative decarboxylative tandem protocols under different Cu catalysts were realized. Abstract : C–N bond formation via a copper-catalyzed aerobic oxidative decarboxylative tandem protocol was realized. The phenylacetic acids which contain ortho -X (X = F or Br) on the aromatic ring will render a fused five-membered heterocycle via a tandem aromatic nucleophilic substitution and aerobic oxidative decarboxylative acylation at the C(sp 2 )–H bond of benzimidazoles under the Cu(OAc)2 /K2 CO3 /BF3 ·Et2 O catalytic system, while with CuBr as the catalyst and pyridine as the base, N -acylation occurred and tertiary amides were obtained.